Job stress and burnout among librarians in selected special libraries in Metro Manila - Mohammad, Satrina V.; Santos, Herminia H. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
Stress may be either functional or dysfunctional in the workplace. It may be viewed as a continuum of stress, distress or strain, and burnout. The sources of job stress and burnout are organizational, and job and career stressors. Stress and burnout manifest in both physical and behavioral occurrences. The level of perceived burnout may vary depending on certain personal and professional characteristics.
This study looks into the prevailing conditions for job stress and burnout in selected special libraries in Metro Manila. It covers libraries in selected government, semi-government, non-government, corporate, and professional organizations.
Among 48 librarians distributed with questionnaires, 37 (77 percent) responded. Majority of the respondents (59.5 percent) were found to be experiencing stress, while 27 percent were distressed or strained. Three (8.1 percent) respondents were found to be burned out. Job-related stressors show a very significant relationship with high levels of burnout. Among the moderating variables, only gender and the number of children are associated with burnout. The most common cited physical effects of burnout are back pains, muscle tension on shoulder, headache, and cold/flu. The most common behavioral manifestations are absenteeism, irritability, and impatience, losing one's temper easily, thinking about resigning from work, and worrying a lot.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Burnout (Psychology).; Libraries -- Job stress -- Philippines -- Manila Metroplitan Area; Special libraries -- Philippines -- Manila Metropolitan Area